2013
DOI: 10.1007/s11914-013-0146-3
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Muscle in Bone Repair: The Cells, Signals, and Tissue Responses to Injury

Abstract: Bone repair is a complicated process that includes many types of cells, signaling molecules, and growth factors. Fracture healing involves a temporally and spatially regulated biologic process that involves recruitment of stem cells to the injury site, tissue specific differentiation, angiogenesis, and remodeling. In light of its proximity to bone and abundant vascularity, muscle is an important potential source of cells and signals for bone healing. More complete understanding of the role of muscle in bone fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 44 publications
0
32
0
1
Order By: Relevance
“…The simplicity of this model compared with a closed or open fracture model (eg, smaller and more confined callus formation, lack of gait defect) supports a direct role for muscle/bone crosstalk in fracture healing [12,19,21,28]. Previous studies using closed and open fracture models have reported conflicting findings over the potential benefit (or lack thereof) of muscle paralysis on fracture healing [3,13].…”
Section: Discussionmentioning
confidence: 73%
“…The simplicity of this model compared with a closed or open fracture model (eg, smaller and more confined callus formation, lack of gait defect) supports a direct role for muscle/bone crosstalk in fracture healing [12,19,21,28]. Previous studies using closed and open fracture models have reported conflicting findings over the potential benefit (or lack thereof) of muscle paralysis on fracture healing [3,13].…”
Section: Discussionmentioning
confidence: 73%
“…Also, there is increasing evidence that skeletal muscle may participate in bone fracture repair. 15 It has recently been reported that skeletal muscle is able to produce a unique type of stem cells which can differentiate into osteoblasts. 15 If muscle at fracture sites could also be effectively infected by AAV-DJ-COX2 vector, the COX2 products generated from the transduced muscle could act on other types of cells participating in fracture repair.…”
Section: Discussionmentioning
confidence: 99%
“…15 It has recently been reported that skeletal muscle is able to produce a unique type of stem cells which can differentiate into osteoblasts. 15 If muscle at fracture sites could also be effectively infected by AAV-DJ-COX2 vector, the COX2 products generated from the transduced muscle could act on other types of cells participating in fracture repair. In fact, the myofibers with slow turnover may provide COX2 products in a sustained period of time compared to the rapidly proliferating cells at fracture site.…”
Section: Discussionmentioning
confidence: 99%
“…The teeth supporting alveolar bone is characterized by distinctive features such as the continuous and rapid remodeling in response to mechanical force stimuli [21] lack of muscle stem cells, which plays a critical role in fracture healing [22,23], healing without histological cartilage formation [24] as well as potential infection of healing alveolar bone due to constant oral microbial challenge surrounding the alveolar bone [25]. Therefore, the characterization of an alveolar bone healing model is important to provide specific insight on alveolar bone healing with different type of BRMs.…”
Section: British Biomedical Bulletin Issn 2347-5447mentioning
confidence: 99%